KOMUNIKASI LINGKUNGAN OLEH DUTA LINGKUNGAN DALAM MELAKSANAKAN PROGRAM PELESTARIAN LINGKUNGAN “SAHABAT SUNGAI PEKANBARU” - Andriva, Africia Wulan; Firdaus, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Environmental Ambassador is a representation of young people who are expected to be able to become influencers in the environmental field. The 1st Runner Up of Environmental Ambassador 2018-2020 has an independent-individual work program namely the Sahabat Sungai Pekanbaru. The existence of the Environmental Ambassador program is expected to be able to assist the Department of Environment and Cleanliness (DLHK) of Pekanbaru City in overcoming problems and campaigning for the environmental love movement in Pekanbaru to the community, especially the younger generation through environmental communication. Therefore this study aims to determine the environmental communication planning of the Environmental Ambassador as a communicator in the environmental protection program